Corporate ownership structure and performance: An enquiry into India - Pradiptarathi PANDA; Jinesh PANCHALI (Theoretical and Applied Economics, 2019)

(untitled)
Influence of corporate ownership structure on corporate performance and governance has been a matter of debate and investigation in the literature of financial performance, and financial economics. This study explores the nature and extent of the relationship between ownership category and financial performance of the firm in limited manner. It investigates as to how heterogeneity of owners as well as the ownership category of the firm, per se, impacts the corporate performance. Employing panel regression model, the results show ownership structure impacts financial performance but only selectively, and the strength of the impact appears weak. This creates a basis for further analysis to understand the incentives and examine the impact of ownership structure on corporate financial performance across the sectors and the markets.